Ensuring conditions for building a low-carbon economy and achieving the Net Zero target by 2050 - TRƯƠNG THỊ MỸ NHÂN; TS ĐINH THỊ NGA (Political Theory Journal, 2026)
The 14th National Party Congress clearly stated: “Build and perfect institutions for ecological environmental protection with the motto 'not trading the environment for economic growth', develop a green economy, circular economy, and low-carbon economy...”. To successfully implement that goal, Vietnam needs to ensure conditions regarding institutions and policies, mobilize diverse resources, especially green financial sources; simultaneously, establish a new growth model linking growth with social justice and environmental protection, effectively responding to climate change.